Gelora: Sosialisasi dan Pelatihan Pembuatan Pakan Lele Alternatif Berbasis Limbah Pertanian Fermentasi di Desa Sebanen - Nasihah, Nila Durrotun; Moch Alvin Najich Robbany; Ningrum, Ria Putri; Salma Affro; Nur Intan Mutiara; Shinta Dhevi Ayu Kusuma Kedhaton; Bella Safira Rachmatika; Muh. Kholid Assaid; Adelia Maharani Putri Suhartono; Betaria Yekti Mumpuni; Rio Agustian Siregar; Muhammad Farhan (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This community service article presents the implementation of the GELORA outreach and training program conducted in Sebanen Village, Jember, Indonesia, focusing on the promotion of low-cost and eco-friendly fermented feeds formulated from locally available agricultural residues such as papaya leaves, rice bran, molasses, and EM4. The program aimed to strengthen the capacity of smallholder catfish farmers and the village enterprise (BUMDes) through a series of integrated activities including a rapid needs assessment, hands-on training sessions, technical mentoring, and knowledge dissemination. As a result, participants demonstrated improved technical skills in household-scale feed formulation and fermentation, a stronger understanding of sustainable and circular economy principles, and an increased willingness to adopt environmentally friendly aquaculture practices. Moreover, follow-up mentoring groups were established to ensure program continuity and local innovation. This participatory model effectively combines community engagement with scientific evidence in aquaculture nutrition and is suitable for replication in other rural aquaculture development contexts.